Harbour seal (Phoca vitulina) PMN and monocytes release extracellular traps to capture the apicomplexan parasite Toxoplasma gondii. Issue 2 (June 2015) - Reichel, Maria; Muñoz-Caro, Tamara; Sanchez Contreras, Guillermo; Rubio García, Ana; Magdowski, Gerd; Gärtner, Ulrich; Taubert, Anja; Hermosilla, Carlos
Highlights: Harbour seal ( Phoca vitulina )-PMN and -monocytes produce extracellular traps. Harbour seal ( Phoca vitulina ) extracellular traps entrapped and immobilised tachyzoites of T. gondii . Fluorescence assays as well as scanning electron microscopy demonstrated harbour seal ET formation. Abstract: Extracellular traps (ETs) are composed of nuclear DNA as backbone adorned with histones, cytoplasmic antimicrobial peptides/proteins which are released from a range of vertebrate and invertebrate host immune cells in response to several invading pathogens. Until now this ancient novel innate defence mechanism has not been demonstrated in any marine mammal. Interactions of harbour seal ( Phoca vitulina )-PMN and -monocytes with viable tachyzoites of Toxoplasma gondii were investigated in this respect in vitro. For the demonstration and quantification of harbour seal PMN- and monocyte-derived ETs, extracellular DNA was stained with Sytox Orange. Fluorescence assays as well as scanning electron microscopy (SEM) analyses demonstrated PMN- and monocyte-promoted ET formation rapidly being induced upon contact with T. gondii- tachyzoites. The co-localisation of extracellular DNA decorated with histones (H3), neutrophil elastase (NE) and myeloperoxidase (MPO) in parasite entrapping structures confirmed the classical characteristics of PMN- and monocyte-promoted ETs. Exposure of harbour seal PMN and monocytes to viable tachyzoites resulted in a significant induction of ETs when compared to negative controls. Harbour seal-ETs were efficiently abolished by DNase I treatment and were reduced after PMN and monocytes pre-incubation with the NADPH oxidase inhibitor diphenilane iodondium. Tachyzoites of T. gondii were firmly entrapped and immobilised within harbour seal-ET structures. To our best knowledge, we here report for the first time on T. gondii -induced ET formation in harbour seal-PMN and -monocytes. Our results strongly indicate that PMN- and monocyte-triggered ETs represent a relevant and ancient conserved effector mechanism of the pinniped innate immune system as reaction against the pathogenic protozoon T. gondii and probably against other foreign pathogens occurring in the ocean environment .